Phenolic acids profile, nutritional and phytochemical compounds, antioxidant properties in colored barley grown in southern Italy. (November 2018) - Suriano, Serafino; Iannucci, Anna; Codianni, Pasquale; Fares, Clara; Russo, Mario; Pecchioni, Nicola; Marciello, Ugo; Savino, Michele
Abstract: Free, soluble conjugated, and insoluble bound phenolic acids and some of the main antioxidant phytochemicals (i.e., total polyphenols, proanthocyanidins, carotenoids) were investigated in 20 genotypes of colored barley. These included 16F8 recombinant inbred lines (RILs) obtained from crosses of four parental lines: '2005 FG', 'K4-31, 'L94', and 'Priora'. The aim of this work was these to promote the introduction of new barley genotypes with high contents of such natural antioxidants, and of dietary fiber. These new genotypes will enlarge the market of novel functional foods. Large variations were seen in the contents of phytochemicals and β-glucans across these barley genotypes. The highest protein (14.4%) and β-glucan (4.6%) contents were in the blue naked parental genotype '2005 FG'. Overall, insoluble bound phenolic acids represented 88.3% of the total phenolic acids, and ferulic acid was the main conjugated phenolic acid. Salicylic and gallic acids were the most represented among the free phenolic acids, with no p -coumaric and cinnamic acids detected. Total polyphenols and proanthocyanidins were highest in the RILs '3009′ (2917 μg g −1 ) and '1997′ (1630 μg g −1 ). The barley line with high total polyphenols (RIL '3009′) also showed the highest antioxidant capacities (by both DPPH and ABTS methods: 13.4 μmol g −1 and 15.6 μmol g −1, respectively). Among the RILs examined, '3004′, '3008′, and '3009′ showed 30% higher antioxidant capacities than their parentals, thus providing potential health-promoting benefits. Graphical abstract: Highlights: Free phenolic acids, conjugated and insoluble bound phenolic acids of 20 colored barley genotypes were studied. Determination of phytochemical main compounds by spectrophotometer and phenolic acids profile by HPLC analysis. Phenolic acids profile was useful in characterization of the 20 barley genotypes High correlation between radical scavenging activity and the total polyphenol content was found.